2015
DOI: 10.1002/2015jd023320
|View full text |Cite
|
Sign up to set email alerts
|

Charged nanoparticles produced by splashing of raindrops

Abstract: The mobility distribution of ions generated by splashing of raindrops is investigated. Our observations show four maxima in the mobility distribution in the small, intermediate, light large, and heavy large ion size ranges. Ion concentration of all categories increases as the rain intensity increases tõ 50-60 mm h À1 and then tends to level off for higher rain intensities. Negative ion concentration is always more than that of positive ions. However, positive small ions of mobility ≥ 2-3 cm 2 V À1 s À1 which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Printer-friendly version Discussion paper measuring small and intermediate ambient ions (Tammet et al, 2009, Laakso et al, 2007Kolarz et al, 2012;Kamra et al 2015) which I can personally confirm.…”
Section: Interactive Commentmentioning
confidence: 90%
“…Printer-friendly version Discussion paper measuring small and intermediate ambient ions (Tammet et al, 2009, Laakso et al, 2007Kolarz et al, 2012;Kamra et al 2015) which I can personally confirm.…”
Section: Interactive Commentmentioning
confidence: 90%
“…In general, the atmospheric nucleation initiates once air ions reached the critical cluster size of 1.5 ± 0.3 nm (Kulmala et al 2013), from that place the growth of a cluster is energetically favored (Vehkamaki 2006). Further, the charged clusters on event days grow faster than the same size neutral particles (Kamra et al 2015a). Kamra et al (2015b) reported the mean growth rates of 3.9-25.3 nm (fraction 12-17) positive (negative) ions to be 49-142% (49-126%) and the growth percentage was more significant for those having size in the range 25.3-47.8 nm (fraction 17-20).…”
Section: Principal Component and Factor Analysismentioning
confidence: 99%
“…In the tropical zone near the Earth's surface, ionization processes are controlled by Radon and its progenies (Hensen and van der Hage 1994). In addition, several other natural sources of small ions production near the ground are corona ions produced in large electric fields, splashing of rain drops at the ground, breaking of water droplets near to the waterfalls and sea shores, dust storms, volcanoes, etc., (Chalmers 1967;Blanchard 1963;Horrak et al 2006;Kolarz et al 2012;Kamra et al 2015a). The mechanism responsible for the production of charge and the nature of atmospheric air ions distributions shows that temporal and spatial variations are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The processes of ion production during rainfall cause an increase in the concentration of small ions in the surface layer. In addition, at that time the concentration of negative ions always prevails over the concentration of positive ions [37][38][39][40]. However, at present, the mechanisms of increasing ions during rain and near waterfalls have not yet been fully understood.…”
Section: Introductionmentioning
confidence: 99%